Anxieties and attitudes of nurses toward death and dying in selected hospitals in Davao and Iligan cities - Evangelista, Teresita N.
Problem: The problems investigated in this study were: 1. What are the nurse's level of anxiety toward death and dying? 2. What factors affect nurses' level of anxiety toward death and dying? 3. What are the nurses' attitudes toward death and dying? Method: Survey. Ss. 217 nurses working in 4 selected hospitals in Davao and Iligan Cities during the period from May 26 to July 15, 1980. Instrument: Questionnaire consisting of personal factors and demographic characteristics (age, civil status, level of nursing education, religious affiliation, religiosity, frequency of contact with the dying and personal experiences on death and dying); on nurses' attitudes towards death and dying (participation in seminars and lectures related to death and dying, willingness to undergo a death education program, and agreement to include death education program in the nursing course); and Templer's Death Anxiety Scale. Statistics: Descriptive analysis, that is, frequency and percentage distribution, and Chi-square test of significance were used. Findings: 1. The highest proportion of nurses in the study have moderate level of death anxiety (104 or 48 ) followed by low level of death anxiety (82 or 38 ) and high level of death anxiety (31 or 14 ). 2. On factors affecting nurses' level of death anxiety, this study showed that there is a significant relationship between levels of death anxiety and nurses' frequency of caring for the dying, nursing position held, religiosity, level of nursing education, area of work, and death experience involving immediate family members. However, factors such as nurses' age, civil status, religious affiliation, size of hospital, frequency of experience of being near death, death experience involving close relatives and friends and their recency of death experience do not affect levels of death axiety. 3. With regards to nurses' attitudes toward death and dying, 47 of the nurses were able to participate in lectures or seminars on abortion, 39 on life sustaining treatment, 35 on death and dying, and 24 on euthanasia. 93 of the nurses are willing and interested to undergo a death education program. Likewise, 89 of the nurses are also agreeable to include death education program in the nursing course.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Nurses -- Attitudes; Death and dying